The impact of the communicative classroom: communicative teaching methods and their impact on key stage 3 learners’ self-efficacy and motivation in the modern foreign language productive skills - Carr, H (2020)
In response to concerns around student engagement with productive tasks in Modern Foreign Languages (MFL), this investigation looks into the impact of three communicative teaching methods on the motivation and self-efficacy of Year 8 learners of French in an inner-city state school. The research aims to identify inclusive teaching methods to enhance engagement in the productive skills. Communicative Language Teaching (CLT) is identified as an approach to look into to achieve this (Mitchell, 1993). Literature reviewed from pedagogical and psychological domains demonstrated the positive impact of increased motivation and self-efficacy and how this might be achieved through a communicative classroom approach. The literature influenced the intervention choices with understandings around motivation and self-efficacy and their relationship with Communicative Language Teaching. The research questions focus on understanding the relationship between CLT, motivation and self-efficacy in language learning. A mixed-method approach is proposed. Student interviews, surveys, task results and classroom observations are planned to take place around a two-phase intervention. The proposed first phase employed three different communicative methods adapted from understandings taken from the literature reviewed: target language use (Christie, 2016), task-based learning (Mutton and Woore, 2014) and flipped learning (Bergmann and Sams, 2007). The two most positively impactful of these methods are then to be combined to create a fourth intervention. A baseline data collection was conducted with the research sample (N=12) through a Likert-scale questionnaire and an interview with participants. Statistical analysis is employed to analyse the motivation and self-efficacy levels of the students. An analysis of variance (ANOVA) was then used to note any significant difference between lower- and higher- attaining students. Research was interrupted by the COVID-19 pandemic. The investigation is therefore, in part, a proposal for future research. The evaluation criteria of post-intervention data taken from questionnaires, interviews, task data and observation notes are presented, but interventions and further data collection to the baseline did not take place. While data collection was interrupted, pedagogical reflections and implications for further research allow the project to remain valuable to professional development.